2014
DOI: 10.5012/bkcs.2014.35.9.2787
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quercetin in the UV-Irradiated Human Keratinocyte HaCaT Cells and A Model of Its Binding To p38 MAPK

Abstract: Quercetin is a major dietary flavonoid found in onions, apples, tea, and red wine, and potentially has beneficial effects on disease prevention. We carried out this study to investigate the effect of quercetin on UVB-induced matrix metalloproteinase-1 (MMP-1) expression in human keratinocyte HaCaT cells and to further understand the mechanisms of its action. The anti-inflammatory activity of quercetin was investigated and quercetin significantly suppressed the NO production in LPS-stimulated RAW264.7 mouse mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In this study, the main components, quercetin, naringenin and taxifolin, were detected in ethanolic extract of PS. In agreement with Jnawali et al (22), our data also showed that quercetin prevented UVB-induced MMP-1 expression via inhibition of phosphorylation of MAPK pathway. On the other hand, naringenin was discovered to inhibit UVB irradiation-induced oxidative stress by upregulation of Nrf2 and HO-1 mRNA levels in hairless mice (29).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the main components, quercetin, naringenin and taxifolin, were detected in ethanolic extract of PS. In agreement with Jnawali et al (22), our data also showed that quercetin prevented UVB-induced MMP-1 expression via inhibition of phosphorylation of MAPK pathway. On the other hand, naringenin was discovered to inhibit UVB irradiation-induced oxidative stress by upregulation of Nrf2 and HO-1 mRNA levels in hairless mice (29).…”
Section: Discussionsupporting
confidence: 93%
“…The cells were exposed to UVB radiation at 144 mJ cm −2 radiation using a UVB irradiation machine (Bio‐Link BLX‐312; Vilber Lourmat GmbH, France) and then were treated with different concentrations of samples. Quercetin was found to be one of the main components of the EPS, and it was introduced as a positive control in this study for that its photoprotective effects against UVB‐induced aging have been studied previously .…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 4 , quercitrin suppressed AGE-induced MMP-1 expression by 30 ± 1.7% and 67 ± 2.0% compared to the control level at the concentrations of 250 μg/mL and 500 μg/mL, respectively. Some studies have found that flavonoid compounds from herbs provided significant inhibitory effects on UVB-induced matrix MMP-1 expression in HaCaT cells [ 39 ]. Similarly, we found quercitrin shows significant activity, indicating that quercitrin plays an important role in MMP-1 inhibitory activity.…”
Section: Resultsmentioning
confidence: 99%
“…5 In addition quercetin content is also found in garlic. 6 Based on the previous researches, this antioxidant was found to be able to reduce skin thickness and wrinkles. This antioxidant content may also maintain the elastin and collagen fibers from the effects of UV light exposure as well as increase the production of type I procollagen.…”
Section: Introductionmentioning
confidence: 99%